Cerebrospinal Fluid Biomarkers in Autopsy-Confirmed Alzheimer Disease and Frontotemporal Lobar Degeneration. (15th March 2022) - Mattsson-Carlgren, Niklas; Grinberg, Lea T.; Boxer, Adam; Ossenkoppele, Rik; Jonsson, Magnus; Seeley, William; Ehrenberg, Alexander; Spina, Salvatore; Janelidze, Shorena; Rojas-Martinex, Julio; Rosen, Howard; La Joie, Renaud; et al.
Abstract : Background and Objectives: To determine how fully automated Elecsys CSF immunoassays for β-amyloid (Aβ) and tau biomarkers and an ultrasensitive Simoa assay for neurofilament light chain (NFL) correlate with neuropathologic changes of Alzheimer disease (AD) and frontotemporal lobar degeneration (FTLD). Methods: We studied 101 patients with antemortem CSF and neuropathology data. CSF samples were collected a mean of 2.9 years before death (range 0.2–7.5 years). CSF was analyzed for Aβ40, Aβ42, total tau (T-tau), tau phosphorylated at amino acid residue 181 (P-tau), P-tau/Aβ42 and Aβ42 /Aβ40 ratios, and NFL. Neuropathology measures included Thal phases, Braak stages, Consortium to Establish a Registry for Alzheimer's Disease (CERAD) scores, AD neuropathologic change (ADNC), and primary and contributory pathologic diagnoses. Associations between CSF biomarkers and neuropathologic features were tested in regression models adjusted for age, sex, and time from sampling to death. Results: CSF biomarkers were associated with neuropathologic measures of Aβ (Thal, CERAD score), tau (Braak stage), and overall ADNC. The CSF P-tau/Aβ42 and Aβ42 /Aβ40 ratios had high sensitivity, specificity, and overall diagnostic performance for intermediate-high ADNC (area under the curve range 0.95–0.96). Distinct biomarker patterns were seen in different FTLD subtypes, with increased NFL and reduced P-tau/T-tau in FTLD–TAR DNA-binding protein 43 and reduced T-tau in progressive supranuclear palsy compared to other FTLD variants. Discussion: CSF biomarkers, including P-tau, T-tau, Aβ42, Aβ40, and NFL, support in vivo identification of AD neuropathology and correlate with FTLD neuropathology. Classification of Evidence: This study provides Class II evidence that distinct CSF biomarker patterns, including for P-tau, T-tau, Aβ42, Aβ40, and NFL, are associated with AD and FTLD neuropathology.